Estudo da redução do índice de acidez de óleos vegetais residuais visando à produção de biodiesel - Souza, André Pereira de (2016)
Waste vegetable oils of gastronomic activities present as contaminants in the environment and of the bodies which it resides, and ascending the disposal of these materials all over the world. The reuse of residual oils in fried foods as raw material for energy generation, more specifically, for the production of biodiesel, forwards as an alternative that meets the environmental, social and economic viabilities. Starting from these assumptions, this referred to work objectively study the desacidification (reducing the acidity index) of waste oil from fried foods collected from the restaurant and cafeteria of the Technology Center (CTEC/UFAL), passing through the steps of agitation with the residual glycerine from biofuels (biodiesel) production in the laboratory of Separation system and optimization (LASSOP/UFAL). For that, the physical and chemical characterization of waste vegetable oil in natura, paying attention to the parameters related to the viscosity, density, humidity, saponification value and acidity index, then the treatment of residual glycerine material targeting the desacidification. Initially the samples were prepared considering the ambient temperature, just by varying the mass of waste vegetable oil and keeping the mass of residual glycerine constant, then were separated samples under the influence of temperatures of 40° C, 50° C and 60° C for the purpose of comparing the interference of this parameter. The analysis showed the feasibility of technology, the acidity indices behave ascendant with the addition of the mass of waste vegetable oil, because the increase of the same implies a greater amount of catalyst to counteract the free fatty acids present in the reaction medium. The material was conducted for biodiesel production, making necessary the standardization and evaluation of income via gas chromatography, reporting percentage 59.6% for biodiesel from waste vegetable oil in natura, 59.0% for biodiesel from oil Treaty with residual glycerine, 64.4% for biodiesel of oil treated with residual glycerine under the influence of temperature of 50oc and 55.8% for biodiesel oil in natura under the temperature of 50oc. The analysis showed the veracity of the process of reduction of the acid value of vegetable oils, but the figures were not satisfactory, because they are lower than the percentages stipulated by regulatory agencies for quality of biofuel.